Targeting Ferroptosis in Tumors: Novel Marine-Derived Compounds as Regulators of Lipid Peroxidation and GPX4 Signaling - Yimao Wu; Xiaoyan Chen; Zichang Chen; Yunqi Ma (Marine Drugs, 2025)
This article reviews the mechanisms by which marine natural products regulate ferroptosis and their potential applications in tumor therapy. Ferroptosis is a form of programmed cell death driven by iron-dependent lipid peroxidation, characterized primarily by the accumulation of lipid peroxides and the failure of antioxidant defense systems. Due to their unique chemical structural diversity, marine natural products demonstrate significant advantages in regulating the ferroptosis pathway. Studies showed that marine compounds target key molecules such as glutathione peroxidase 4 (GPX4) and long-chain acyl-CoA synthetase 4 (ACSL4(a)) ACSL4(1) to modulate lipid peroxidation and iron metabolism, inducing ferroptosis in tumor cells and reshaping the tumor microenvironment (TME). In addition, marine compounds can enhance anti-tumor effects by activating immune responses. Although marine compounds hold great potential in regulating ferroptosis, their clinical translation faces challenges such as low bioavailability and tumor type dependency. Future research needs to integrate multi-omics techniques to further analyze the mechanisms of marine compounds and develop precision therapeutic strategies based on marine compounds to overcome the bottlenecks in ferroptosis therapy.